RENCANA BISNIS PENGEMBANGAN USAHA APLIKASI “O-BRIDGE” APLIKASI PENYEDIA VENDOR JASA - Egadhana, Ezra; Ferry, Nopgriyana; Budiarti, Ratna; Rohmah, Siti; Leny, Novia Sulistyo; Magdalen, Martha (Journal of Entrepreneurship, Management and Industry (JEMI), 2019)
The topic in the writing of this article is the business plan of an application-based business called O-Bridge that functions as a liaison between service provider vendors and also people who need to use services. This application was created with the mission of facilitating economic activities related to services. This article serves to identify, analyze and also plan business along with predictions of O-Bridge's financial viability. This method of analyzing business uses a SWOT analysis, Business Model Canvas and also a market mix or marketing mix.